2019
DOI: 10.1186/s13227-019-0121-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel budding mode in Polyandrocarpa zorritensis: a model for comparative studies on asexual development and whole body regeneration

Abstract: Background In tunicates, the capacity to build an adult body via non-embryonic development (NED), i.e., asexual budding and whole body regeneration, has been gained or lost several times across the whole subphylum. A recent phylogeny of the family Styelidae revealed an independent acquisition of NED in the colonial species Polyandrocarpa zorritensis and highlighted a novel budding mode. In this paper, we provide the first detailed characterization of the asexual life cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…While in Botrylloides leachii they express the stem cell markers Piwi2 and Vasa (Kassmer et al, 2019), Vasa and Piwi1 are not expressed in vascular buds of Botryllus primigenus (Sunanaga et al, 2006(Sunanaga et al, , 2010, while Piwi proteins are only detected in some peripheral cells of vascular bud in Botrylloides violaceus (Brown, Keeling et al, 2009). The third form of NED reported in Stolidobranchia is vasal budding (Figures 1 and 2g), recently described only in Polyandrocarpa zorritensis (Alié et al, 2018;Brunetti & Mastrototaro, 2004;Scelzo et al, 2019). Vasal buds appear along a stolon, which consists of a blood vessel up to several centimeters long, protruding from the epidermis of the parental zooid and covered by a thin layer of the tunic.…”
Section: Budding In Stolidobranchia: the Peribranchial The Vascular… And The Vasalmentioning
confidence: 96%
See 1 more Smart Citation
“…While in Botrylloides leachii they express the stem cell markers Piwi2 and Vasa (Kassmer et al, 2019), Vasa and Piwi1 are not expressed in vascular buds of Botryllus primigenus (Sunanaga et al, 2006(Sunanaga et al, , 2010, while Piwi proteins are only detected in some peripheral cells of vascular bud in Botrylloides violaceus (Brown, Keeling et al, 2009). The third form of NED reported in Stolidobranchia is vasal budding (Figures 1 and 2g), recently described only in Polyandrocarpa zorritensis (Alié et al, 2018;Brunetti & Mastrototaro, 2004;Scelzo et al, 2019). Vasal buds appear along a stolon, which consists of a blood vessel up to several centimeters long, protruding from the epidermis of the parental zooid and covered by a thin layer of the tunic.…”
Section: Budding In Stolidobranchia: the Peribranchial The Vascular… And The Vasalmentioning
confidence: 96%
“…Budding and nonbudding species are scattered among the four main tunicate orders: Thaliacea, Phlebobranchia, Aplousobranchia, and Stolidobranchia, and their phylogenetic distribution unambiguously demonstrates that asexual reproduction arose convergently several times (Alié et al, 2018; Delsuc et al, 2018; Govindarajan, Bucklin, & Madin, 2011; Kocot, Tassia, Halanych, & Swalla, 2018; Pérez‐Portela, Bishop, Davis, & Turon, 2009; Shenkar, Koplovitz, Dray, Gissi, & Huchon, 2016; Tsagkogeorga et al, 2009). Convergent acquisition of NED becomes even more evident by the variety of tissues and mechanisms involved in bud formation across the different species (Berrill, 1951; Godeaux, 1957; Oka & Watanabe, 1957; Scelzo, Alié, Pagnotta, & Tiozzo, 2019). In fact, in contrast to embryonic development, which shows an extraordinary level of conservation amongst almost all the main tunicate orders, nonembryonic developmental processes involve a variety of cells, tissues, and ontogenesis, all displaying different degrees of interaction between epithelial and mesenchymal cells (even within a single order).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple cases of HGT were reported, for example, in nematodes [31][32][33], rotifers [34][35][36] and cnidarians [37]. Tunicates, a basal chordate group, are exceptional in their use of various ways of asexual reproduction [38,39]. Previous studies revealed two proposed cases of HGT from prokaryotes to tunicates [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Convergent rather than homologous evolution of coloniality in the family Styelidae is indicated by two strong lines of evidence. First, Botryllinae + Polyzoinae create colonies through peribranchial budding [36,37], with Botryllinae + Symplegma in the Polyzoinae also capable of vascular budding [38,39], whereas P.zorritensis is unique among the tunicates in its use of vasal budding [40]. Second, an evolution of coloniality in the most recent common ancestor of Botryllinae, Polyzoinae, and P.zorritensis would contradict the principle of parsimony, requiring four to six character state changes [36].…”
Section: Coloniality In Order Stoliobranchiamentioning
confidence: 99%